Hb East Timor [ß80(EF4)Asn?His, AAC>CAC (HBB c.241A>C)], a variant hemoglobin associated with normal hematology - Finlayson, J.; Ghassemifar, Reza; Holmes, P.; Grey, D.; Figliomeni, L.; Newbound, C.; Pell, N.; Kersten, M.; Jennens, M.; Macaulay, C.; Greenwood, L.; Beilby, J. (Taylor and Francis Ltd, 2010)
Routine hemoglobin (Hb) analyses identified a new ß-globin variant in a family from East Timor. The red cell indices were within normal limits for all affected family members. The variant is due to a missense mutation at amino acid codon 80 (AAC>CAC) which results in the substitution of histidine for asparagine. © 2010 Informa Healthcare USA, Inc.